Ethical burdens of COVID-19 testing: the case for a research agenda to improve effectiveness and equity in pandemic response - Dana Howard; Dana Howard; Abigail Norris Turner; Julianna Nemeth; Tasleem J. Padamsee (Frontiers in Public Health)
US public health response to COVID-19 has focused on increasing availability and access to viral testing, which raises three sets of potential problems: (1) lack of testing uptake, (2) diminished public health impact of testing, and (3) loss of access to necessary social goods and supports. Moreover, these problems are encountered differentially in affluent vs. disadvantaged communities. If not addressed, these problems could exacerbate health disparities via the public health strategies that aim to lower the population-level impact of COVID. These problems also risk undermining trust in public health interventions more broadly and pose challenges to the sustainability of testing programs moving forward. In this perspective essay, we argue that public health research must aim to document and understand the mechanisms through which living in structurally disadvantaged environments exacerbates not only the logistical and material burdens of COVID-19 testing, but also the ethical and social burdens it creates. Such research will facilitate development of targeted interventions that empower people to make the testing-related decisions that best serve both their own interests and those of their broader communities.